1982
DOI: 10.1038/bjc.1982.122
|View full text |Cite
|
Sign up to set email alerts
|

Human tumour xenografts in athymic rats and their age dependence

Abstract: Images Fig. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…The slow growth oftumors in the young animals and the lack of growth in older animals is consistent with observations that nude rats have elevated natural killer cell activity and extrathymic Tcell differentiation that occurs in an age-related fashion 24,25 Prior reports have shown that whole-body irradiation significantly increases take rates for subcutaneous tumor xenografts in nude rats. 26 To improve acceptance of the Fischer 11-45 tumor implantation in athymic nude rats, we further immunosuppressed these animals with 500 cGy of whole-body irradiation on the day of tumor implantation.…”
Section: Adenoviral Vectorssupporting
confidence: 64%
“…The slow growth oftumors in the young animals and the lack of growth in older animals is consistent with observations that nude rats have elevated natural killer cell activity and extrathymic Tcell differentiation that occurs in an age-related fashion 24,25 Prior reports have shown that whole-body irradiation significantly increases take rates for subcutaneous tumor xenografts in nude rats. 26 To improve acceptance of the Fischer 11-45 tumor implantation in athymic nude rats, we further immunosuppressed these animals with 500 cGy of whole-body irradiation on the day of tumor implantation.…”
Section: Adenoviral Vectorssupporting
confidence: 64%
“…The take rates for cells from previously serially transplantable tumour lines or from primary explants have been reported to be equal in rats and mice (Sawada et al, 1982;Matthews et al, 1982). However, in a few studies the take rates have been observed to be lower in nude rats (Maruo et al, 1982;Giovanella et al, 1984). In addition, the take rate (Sawada et al, 1982;Maruo et al, 1982;Drewinko et al, 1986) and growth rate (Maruo et al, 1982) of xenografts in nude rats have been observed to decrease with increasing age in the animal.…”
Section: Discussionmentioning
confidence: 94%
“…However, in a few studies the take rates have been observed to be lower in nude rats (Maruo et al, 1982;Giovanella et al, 1984). In addition, the take rate (Sawada et al, 1982;Maruo et al, 1982;Drewinko et al, 1986) and growth rate (Maruo et al, 1982) of xenografts in nude rats have been observed to decrease with increasing age in the animal. This decrease of take rate and growth rate is thought to be related to the observed increase of host NK cell activity with ageing in the nude rat (Lotzova et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In most previously published orthotopic animal models of human GBM (Rana et al 1977;Bradley et al 1978;Shapiro et al 1979;Bullard et al 1981;Horten et al 1981;Jones et al 1981;Basler and Shapiro 1982;Marno et al 1982;De Armond et al 1994), the tumors were implanted not in solid pieces but by stereotaxic injection of cell suspensions. The cell suspension methods of grafting have the distinctive advantage of limited surgical trauma.…”
Section: Discussionmentioning
confidence: 99%